Prevalence and Antibiotic Susceptibility of Gram-Positive, Gram-Negative Bacteria and Candida in UTI Clinical Samples - Ameer A. Karim; Alaa H. Abd Ali; Enas K. Alkhazraji; Sajjad S. Hameed (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Urinary tract infections (UTIs) are among the most common infections affecting the urinary system, including the urethra, kidneys, and bladder. Specific Background: In Iraq, the spectrum of UTI pathogens and their antibiotic resistance patterns remain insufficiently characterized, particularly in Al-Najaf province. Knowledge Gap: Limited data exist on the distribution of gram-positive, gram-negative, and fungal uropathogens alongside their antibiotic susceptibility profiles in both male and female outpatients in this region. Aims: This study aimed to identify the pathogen spectrum of UTIs, determine the distribution in women and men, and evaluate antibiotic resistance levels of isolated strains. Results: Among 618 outpatients, the most clinically significant microorganisms were Staphylococcus aureus (27.3%), Escherichia coli (25.4%), Staphylococcus epidermidis (17.0%), Streptococcus spp. (16.3%), and Candida albicans (6.1%). Women accounted for 89.8% of infections; C. albicans was detected only in women (6.1%). Highest resistance was observed to cefotaxime (up to 100% in Pseudomonas aeruginosa). Vancomycin (2% resistance) and amikacin (6-39% resistance) were the most effective antibiotics, with amikacin particularly effective against gram-negative bacteria. Novelty: This study provides the first comprehensive UTI pathogen and resistance profile from Al-Sajjad Hospital, Najaf, revealing S. aureus as the predominant pathogen over E. coli, contrasting with global trends. Implications: Empirical UTI therapy in this region should consider vancomycin and amikacin as potential options while avoiding cefotaxime, and clinicians should recognize the high female predominance and unique pathogen hierarchy. Highlights : Staphylococcus aureus (27.3%) outnumbered Escherichia coli (25.4%) as the leading UTI pathogen in Al-Najaf, Iraq. Candida albicans (6.1%) was detected exclusively in female patients with UTIs. Cefotaxime resistance reached 100% in Pseudomonas aeruginosa, while vancomycin showed only 2% resistance across gram-positive cocci. Keywords: Urinary Tract Infections, Antibiotic Resistance, Staphylococcus Aureus, Escherichia Coli, Iraq